Controlled release urea altered the paddy soil heterogeneity at mesoscale qualified by laser induced breakdown spectroscopy - Ma, Fei; Zhou, Jianmin; Du, Changwen (Geoderma, 2024)
[Display omitted] •LIBS was employed to capture soil heterogeneity at mesoscale.•PCA method and ternary plots explored main elements distribution.•RGB method was applied to qualify soil heterogeneity.•Controlled release urea altered the paddy soil heterogeneity at mesoscale. Farmland soil shows strong heterogeneity due to crop rotations and fertilizer inputs, and characterization of soil heterogeneity will benefit understanding soil management. In this study, the technique of laser induced breakdown spectroscopy (LIBS) was used to investigate the heterogeneity of paddy soil in-situ at mesoscale (20 μm ∼ 2 mm) under long term input of controlled release nitrogen. Principal component analysis (PCA) of LIBS spectra interpreted elements distribution in the first three PCs. PC1 contained higher proportions of K, O, Al, Si, Na, Ca and Mg information (more than 50 %), PC2 contained more proportions of Li, Ti, Fe, K, Mg and Si information (40 %), and PC3 contained more proportions of Ca, Mg, Mo, Ti and Pb information (35–40 %). The Red-Green-Blue composite using PC1, PC2 and PC3 as color codes was constructed. Soil heterogeneity was in-situ visualized by color blending maps at mesoscale and the hierarchical cluster analysis showed that increasing input of controlled released nitrogen altered soil heterogeneity. Therefore, LIBS provided a method to achieve a digital description of soil heterogeneity at mesoscale, which could be an alternative option to capture spatio-temporal soil information for evaluating the effects of agricultural management on soil quality.